The Factors of Administrative Division in the Light of International Experiences as an Entry Point for Local Development: A Comparative Study - El Sherif, Adel; El Khawaga, Dina (The Arab Journal of Administration, 2025)
Purpose: Due to the low rates of local development, especially in developing countries, the aim of this research is to study the elements of the administrative division unit, to reach scientific and practical factors for the administrative division and its modifications, whether they have a direct or indirect effective impact on local development rates through international experiences in China, South Africa, and Denmark. Methodology: The research relied on comparing and benefiting from international experiences, and identifying the effective and clearly influential factors of administrative division on local development. By studying each element of the administrative unit (territory, population and local government) in the three countries to determine how each of these elements affected local development. Finally, deduce the factors that can be used to conduct effective administrative division on local development. Results: The study found two factors that must be taken into account when making a new administrative division or making an amendment to an existing administrative division. The first factor is “the territory” based on the fact that “the economically quality of the territory, attracts the population.” It was found that the increase in population affects the administrative division in two forms, the first is an increase in the number of basic administrative units, urban centers and cities, and the second is an increase in the number of administrative levels. That is, the quality of the region indirectly affects the horizontal and vertical form of the administrative division. And that the higher the quality of the region of the administrative division. The second factor is the degree of social homogeneity. Since ethnic, religious or linguistic homogeneity, affects the stability of the population. It was found that the greater the stability of the community, the greater the effectiveness of the population on local development within the unit of administrative division. The study found that local government is not a factor on which administrative division is built. The organization of the local government and its use of decentralization mechanisms depends on the state’s system of government, the constitution and laws regulating the state.